Calculation of Macroscopic Effects of Quantum Gravity in General Static Isotropic Gravitational Fields (Global Journal of Science Frontier Research, 2024)
In this paper we calculated the self-interaction of the gravitational field in coordinate space by approximate method, and find the functional relationship between gravitational source and distance and selfinteraction of quantum gravity. The calculation result shows that the self-interaction of quantum gravity can explain the gravitational effects of dark matter. In the solar system, the self-interaction is extremely weak, but it is enough to explain the the Pioneer anomaly.
Keywords: gravitational source and distance and self-interaction of quantum gravity